1993
DOI: 10.1021/j100110a021
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer reactions of triplet 9-arylxanthenium and 9-arylthioxanthenium cations

Abstract: Triplet excited states of 9-arylxanthenium and 9-arylthioxanthenium cations have been characterized using laser flash photolysis. The triplet cations absorb at -300 nm and are long-lived ( T > 5-10 ps) in the absence of electron donors. They undergo efficient electron transfer reaction with a variety of aromatic donors, including biphenyl, naphthalene, substituted benzenes, and the precursor alcohols, to give the corresponding xanthenyl or thioxanthenyl radicals and the radical cation of the aromatic donor. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
1
17
1
Order By: Relevance
“…However in molecules with electron poor aromatic substituents this photoinduced electron transfer process is shut down due to the electron deficient aryl rings and hence CRTs with electron poor aryl rings has higher fluorescence quantum yield compared to the CRTs with electron-rich substituents. Moreover, due to higher excitation energy of the singlet state the singlet excited state is more oxidizing compared to the triplet excited state [58].…”
Section: Photochemistry and Photophysics -Fundamentals To Applicationsmentioning
confidence: 99%
“…However in molecules with electron poor aromatic substituents this photoinduced electron transfer process is shut down due to the electron deficient aryl rings and hence CRTs with electron poor aryl rings has higher fluorescence quantum yield compared to the CRTs with electron-rich substituents. Moreover, due to higher excitation energy of the singlet state the singlet excited state is more oxidizing compared to the triplet excited state [58].…”
Section: Photochemistry and Photophysics -Fundamentals To Applicationsmentioning
confidence: 99%
“…However, the yield of net electron transfer (ф et ) process is found to be very small (≤ 0·02) due to efficient back electron transfer reaction between the products of the photo-induced electron transfer reactions, i.e., 9-phenylxanthenyl radical and radical cation of the corresponding reactant. Even though the singlet excited state of PX+ has been studied extensively by monitoring the fluorescence of the system, barring a couple of papers by Johnston and Wong, 17,18 there is hardly any literature dealing with the triplet state of this system. In these papers, the authors have characterized the triplet-triplet absorption spectra of PX+ by generating this species from PX in the presence of varied concentrations (1-10 mM) of trifluoroacetic acid.…”
Section: Introductionmentioning
confidence: 99%
“…In these papers, the authors have characterized the triplet-triplet absorption spectra of PX+ by generating this species from PX in the presence of varied concentrations (1-10 mM) of trifluoroacetic acid. 17,18 They found that *For correspondence the triplet-triplet absorption due to PX+ shows maximum xat < 300 nm and is characterized by a lifetime of several microseconds. The exact lifetime depends on the concentration of PX in the medium (which can be varied by adjusting the concentration of the added acid) as PX+ triplet undergoes electron transfer reaction with PX and produces 9-phenylxanthenyl radical, which can be characterized by the 340 nm band in the transient absorption spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations